2005
DOI: 10.1080/02640410410001729919
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variation in cycling performance: Influence of warm-up

Abstract: We examined the effects of time of day on a cycling time trial with and without a prolonged warm-up, among cyclists who tended towards being high in "morningness". Eight male cyclists (mean +/- s: age = 24.9 +/- 3.5 years, peak power output = 319 +/- 34 W, chronotype = 39 +/- 6 units) completed a 16.1-km time trial without a substantial warm-up at both 07:30 and 17:30 h. The time trial was also completed at both times of day after a 25-min warm-up at 60% of peak power. Power output, heart rate, intra-aural tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
75
1
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(90 citation statements)
references
References 27 publications
9
75
1
4
Order By: Relevance
“…In studies that support the findings of our study, the physical performance of swimmers [41] and cyclists [30,42] was reported to gradually increase throughout the day, and a positive correlation with body temperature was found. In a study on the comparison of body temperature and jumping score at 10:00 and 17:00, body temperature (36.9 vs. 37.2°C; p < 0.001) and peak power output of jumping (5248 vs. 5413 W; p < 0.001) were found to increase at 17:00.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In studies that support the findings of our study, the physical performance of swimmers [41] and cyclists [30,42] was reported to gradually increase throughout the day, and a positive correlation with body temperature was found. In a study on the comparison of body temperature and jumping score at 10:00 and 17:00, body temperature (36.9 vs. 37.2°C; p < 0.001) and peak power output of jumping (5248 vs. 5413 W; p < 0.001) were found to increase at 17:00.…”
Section: Discussionsupporting
confidence: 78%
“…Some other factors like age, the type and intensity of exercise, jet-lag, and sleeplessness also affect these daily changes [15,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Noutros cinco estudos verifica-se a interferência dos ritmos circadianos em algumas das variáveis estudadas, mas não em todas elas (Martin et al, 2001;Atkinson et al, 2005;Bessot et al, 2006;Hobson et al, 2009, Kunorozva et al, 2014.…”
Section: -4-exercícios De Longa Duração (Superiores a 5 Minutos)unclassified
“…Oxygen consumption and heart rate at the lactate threshold intensity 39) Time to exhaustion in the heat 42) 16.1-km cycling time trial 41) Short-term power output 27,28) No time of day variation Adverse cardiovascular events 45,46,55,56) Exercise-induced adverse cardiovascular events 57,58) Higher risk in the morning than in the afternoon and evening…”
Section: Safetymentioning
confidence: 99%
“…Interestingly, studies examining other indices of endurance capacity have demonstrated a circadian rhythm or diurnal variation suggesting evening superiority: higher oxygen consumption and heart rate at the lactate threshold intensity 39) , higher aerobic contribution to energy production during 30 seconds of maximal pedaling 40) , and a faster record in a 16.1 km cycling time trial (about 23 minutes) 41) .…”
Section: A Variety Of Human Circadian Rhythms and Characteristicsmentioning
confidence: 99%